USE OF FOLK PEDAGOGICAL RESOURCES IN CHILD EDUCATION (American Journal of Pedagogical and Educational Research, 2024)
In this article, the primary tasks of parents in child education were explained based on educational technologies and methods of education that should be used for raising children in the family in accordance with today's innovative technologies.